(3GdMbjbI hGdeLGR aj QMdI HdGO GdTGe heUQ hGdMLGRs - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd dbO cfJ ajeG JbOe ef GdReGf eY LedI ef GdCUMGH s
(3BNQgG (B:s
(3hUOjbfG YHO GdhgGH GHf GdTjN YHO GdQMef hGdTjN MLGRi dg TQM Ydi GdLGeY GdUZjQ s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYOI NWhWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B412s
Keywords: (3GdLZQGajG h GdHdOGfs